[Fancy Indian] - Jolly, M. (My University, 2009)
Description on the back of postcard: “A colourful and fantastic Carnival costume snapped during Carnival time at Arima, a town 17 miles from Port of Spain.” This masquerader portraying a Fancy Indian is wearing a headpiece that is filled with feathers. Postcard numbered C10734.
Colour: Coloured; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Carnival--Trinidad and Tobago; Carnival costume--Trinidad and Tobago; Festivals--Trinidad and Tobago; Popular culture--Trinidad and Tobago